Microstrip Patch Antenna Design and Performance Study for Biomedical Application - Elgheriani, Anas Abdulbasit Masoud (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Early stage of tumor detection is important due to increased chance for recovery and saving patient's lives, therefore, many types of researches are going out to find more techniques or methods to be used for breast cancer detection in early stages. The aim of this thesis is to investigate the tumor location after designing a UWB antipodal Vivaldi antenna. In this thesis, an antipodal Vivaldi antenna has been designed using copper for patch and ground layers and FR4 for the substrate layer. The antenna is operating over a band from 3.38 to 10GHz. Also the antenna parameters which are reflection coefficient (S11), directivity and radiation pattern are included in this study. Moreover, to optimize the antenna radiation direction and reduce the sidelobe leve, a Tapered Slot Edge (TSE) technique is applied and shows -18.8 dB and 6.58 dBi for side lobe level and directivity respectively at 5 GHz. The Specific Absorption Rate (SAR) is the tool used to indicate the tumor location in the coordinate system (x, y, z) in this research. Tests have been done with CST microwave studio using a breast model built with a radius of 50mm. For simulation tumor radius was changed from 10mm, 7mm and 5mm respectively. Also the antenna location changed to 3 different places for reliability. The tumor location is approximated to the same coordinates of the maximum specific absorption rate (SAR) which is examined at 5GHz, 6GHz, 7GHz and 8GHz. Simulations successfully show the correct tumor location while the antenna is facing the tumor. Keywords: Antipodal Vivaldi Antenna, Tapered Slot Edges (TSE), Specific Absorption Rate (SAR), Tumor Detection and Coordinates.

ÖZ: Tümör tedevisinde, hastaların hayatını kurtarabilmek için erken tanı çok önemlidir ve meme kanserinin erken teşhisi için çeşitli araştırmalar yapılmaktadır. Bu araştırmaların neticesinde erken tanıyı sağlayabilecek teknik veya methodlar geliştirilmektedir. Bu tezin amacı UWB antipodal Vivaldi anteni tasarlayarak tümörün hasta vücudundaki yerini tespit etmektir. Bu tezde, patch ve yer katmanları için bakır, alt tabakalar için FR4 kullanılarak bir antipodal Vivaldi anteni tasarlanmıştır. Tasarlanan anten 3.38 GHz ile 10 GHz arasında çalışmaktadır. Ayrıca, yansıma katsayısı (S11), directivity, radiation pattern gibi anten parametreleri çalışmaya dahil edilmiştir. Antenin radyasyon yönünü optimize etmek ve yan lob levelini düşürmek için Tapared Slot Edges (TSE) tekniği kullanılmıştır ve yan lobda -18.8 dB ile 6.58 dBi gözlemlenmiş olup directivity 5 GHz olarak gösterilmiştir. Bu çalışmada, tümör lokasyonunu koordinat sisteminde (x, y, z) göstermek için Specific Absorption Rate (SAR) yöntemi kullanılmıştır. Simülasyonlar CST microwave kullanılarak yapılmıştır ve göğüs modeli 50 mm yarı çapı olacak şekilde kurulmuştur. Simülasyonlar, tümörün yarı çapı 10 mm, 7 mm ve 5 mm seçilerek gerçekleştirilmiştir. Ayıca, güvenirlik açısından tümörün lokasyonu 3 farklı yere konuşlandırılmıştır. Tümör lokasyonları aynı maksimum SAR kordinatlarında seçilerek 5 GHz, 6 GHz, 7 GHz ve 8 GHz frekanslarında denenmiştir. Sonuç olarak, anten tümör ile karşılaşınca lokasyonları başarılı bir seşilde tespit edebilmiştir. Anahtar Kelimeler: Antipodal Vivaldi Anteni, Tapered Slot Edges (TSE), Specific Absorption Rate (SAR), Tümör Tespiti and Koordinatlar.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2020. Supervisor: Prof. Dr. Şener Uysal
Keywords: Electrical and Electronic Engineering; Microstrip antennas--Design and construction; Antipodal Vivaldi Antenna; Tapered Slot Edges (TSE); Specific Absorption Rate (SAR); Tumor Detection and Coordinates